The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1124/jpet.109.155069
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Attenuates Amyloid β25–35Peptide-Induced Memory Impairments: Implication of Inducible Nitric-Oxide Synthase and Tumor Necrosis Factor-α in Mice

Abstract: In Alzheimer's disease (AD), the deposition of amyloid peptides is invariably associated with oxidative stress and inflammatory responses. Silibinin (silybin), a flavonoid derived from the herb milk thistle, has potent anti-inflammatory and antioxidant activities. However, it remains unclear whether silibinin improves amyloid ␤ (A␤) peptide-induced neurotoxicity. In this study, we examined the effect of silibinin on the fear-conditioning memory deficits, inflammatory response, and oxidative stress induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…In this view, silibinin should not interfere with the anticancer property of oxaliplatin. 41 The present data highlight the anti-neuropathic properties of silibinin which, together with its protective effects in hepatic diseases 15,30,31,44 as well as in neurodegenerative disorders, 31 suggest its clinical applicability as an adjuvant in cancer patients to prevent or reduce chemotherapy-induced toxicity. The protective effects and the anticancer activity confer to silibinin a ubiquitous profile that differentiates this molecule from other antioxidant drugs clinically used to treat oxaliplatin-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 75%
“…In this view, silibinin should not interfere with the anticancer property of oxaliplatin. 41 The present data highlight the anti-neuropathic properties of silibinin which, together with its protective effects in hepatic diseases 15,30,31,44 as well as in neurodegenerative disorders, 31 suggest its clinical applicability as an adjuvant in cancer patients to prevent or reduce chemotherapy-induced toxicity. The protective effects and the anticancer activity confer to silibinin a ubiquitous profile that differentiates this molecule from other antioxidant drugs clinically used to treat oxaliplatin-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 75%
“…Nabeshima et al recently reported that silibinin, a component of silymarin, prevents acute and subchronic memory loss induced by the intraventricular injection of A25-35 into mice, due to its strong free radical- scavenging activity 57) and its inhibition of nitric-oxide synthase and tumor necrosis factor-. 58) However, no data on AD pathology due to silibinin were given in these reports. The differences in the protective effects of silibinin and silymarin on memory task might be explained by distinct protocols of material (a component of silymarin or crude extract), duration (11 d or 6 months), and in vivo model (acute model by exogenous A injection or chronic model by APP transgene), respectively.…”
Section: Discussionmentioning
confidence: 89%
“…In the same mice model, Alkam et al (2008) showed an increase of mnesic performances in novel object recognition task after thalidomide treatment, a degrader of TNF-␣ mRNA, or intracerebroventricular injection of an anti-TNF-␣ antibody. Recently, Lu et al (2009a) demonstrated that silibinin, a flavonoid, attenuates memory impairment in cued and contextual fear-conditioning test, through amelioration of oxidative stress and inflammatory response induced by an intracerebroventricular injection of A␤25-35. In a clinical open-label pilot study, perispinal use of a TNF-␣ inhibitor, etanercept, in AD patients claimed detectable improvement of cognitive performance (Tobinick et al, 2006).…”
Section: Discussionmentioning
confidence: 99%